INVESTIGATING EFL LEARNERS’ ABILITY IN ANALYZING SEMANTIC OF ADVERTISEMENT TAGLINES: A LINGUISTIC ANALYSIS AT STIBA PERSADA BUNDA PEKANBARU - Vina Fathira; Silvia Utami (Universitas Negeri Padang, 2018)
In this digital era, it is good to investigate the semantic in advertisements as media in learning linguistics since the learners are familiar to look at some advertisements. In this research, the researchers wanted to investigate the learners’ ability in semantic of advertisements. This research aims at investigating EFL learners’ understanding in analyzing semantic of taglines in advertisements. In this research, the researchers used qualitative method explained descriptively. In collecting data, learners were asked to analyze 3 different taglines of advertisements. In analyzing data, the researchers counted the score into range given at STIBA Persada Bunda Pekanbaru. The result showed that most of the learners are in good level, since only a few learners are in fairly good. It means that the learners are more easily to get semantic meaning of taglines of advertisements. Findings of the research that had been analyzed by the learners were divided into two things. First, it was easy for the learners to analyze since the advertisements are familiar to see by the learners. Second, only a few learners are difficult to understand the semantic of taglines of advertisements since the learners are dislike and rarely watching advertisement in television or other media.